PERBEDAAN KEMAMPUAN SPASIAL BERDASARKAN GENDER MELALUI PENGGUNAAN MEDIA PAPAN BERPAKU DI SEKOLAH DASAR - Luthfiyah Maulidina; Nila Kesumawati; Nurlela (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Mathematics is a subject that is useful in everyday life and can train and improvestudents thinking skills. However, many students feel that mathematics is adifficult subject to understand. As a result, students tend to avoid learningmathematics, which leads to low thinking abilities. The purpose of this study wasto determine the influence of geoboard media on students’ spatial abilities basedon gender at SDN 30 Palembang. The method used was a quantitative experimentwith a posttest-only control group design. The population of the study consisted ofall fourth-grade students at SDN 30 Palembang, totaling 123 students. The samplewas taken from class IV A as the experimental group using geoboard media, andclass IV D as the control group that did not use the media. Each class consisted of32 students selected randomly. Data were collected through a spatial ability test,and data analysis was performed using two-way ANOVA. The results of the studyshowed: 1) There is an influence of using geoboard media on students spatialabilities at SDN 30 Palembang. 2) There is no difference in spatial ability based onstudents' gender at SDN 30 Palembang. 3) There is no interaction betweengeoboard media and gender on students spatial abilities at SDN 30 Palembang